(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The convening of the Madrid peace conference came in light of international changes, the most important of which was the fall of the Soviet Union and the transformation of world politics into a unipolar policy led by the United States of America, in addition to the changes that the Arab region witnessed, such as the occurrence of the Palestinian uprising in 1987 AD and the Iraqi-Kuwaiti war in 1990 and its negative effects on Arab-Arab relations. In general, the Arab-Palestinian region in particular, which led to the fall of the Arab region under American control. The research touched on the reasons and circumstances that led to the convening of the Madrid Peace Conference, clarifies the foundations on which the conference was based, and the concerned parties ’position on calling for its convening. It also sheds light on the nature of the negotiations that took place between those parties, in addition to showing the implications for the Palestinian issue. Searching for a conclusion that holding this conference was to serve the Israeli interests and liquidate the Palestinian cause.